Menjaga Hak Pemegang Polis: Perlindungan Hukum Terhadap Pailitnya Perusahaan Asuransi - Imam Buchari (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This paper aims to analyze the Preventive and Repressive Legal Protection for Insurance Policyholders against Bankrupt Insurance Companies. Using a normative legal research method with a conceptual approach, the study reveals that preventive protection involves insurance companies maintaining a guarantee fund, constituting a safety net for potential liquidity issues. The fund, at least 20% of the minimum equity set by the Financial Services Authority, ensures the fulfilment of insurance obligations. Another aspect of protection includes OJK educating the public and recommending insurers with liquidity exceeding 120% of the Minimum Capital Adequacy Ratio. Repressive actions, handled by a curator managing the bankrupt estate, prioritize policyholders' rights in the event of liquidation. OJK can impose administrative sanctions, such as revoking business licenses, enabling policyholders to claim their rights through bankruptcy proceedings.